Pengaruh Brand Experience, Brand Trust, Customer Satisfaction Terhadap Brand Loyalty Produk Cimory - Maria Yoana dan Miharni Tjokrosaputro (Universitas Tarumanagara, 2019)
Over time, the company experienced intense business competition between companies. This competition is also experienced by consumer goods companies namely food and beverage companies, including fermented milk companies or yogurt. The company strives to carry out a marketing strategy to be able to deal with its competitors. Therefore, company management must have a specific strategy for making products, maintaining products and generating customer satisfaction, which will thus lead to high loyalty from consumers to the products released by the company. One company that is experiencing business competition is Cimory. Cimory produces yogurt with a variety of flavors, and its competitors are Yakult who have been in Indonesia for a long time. This study will discuss how the influence of brand experience, brand trust, Cimory's customer satisfaction on brand loyalty in the eyes of consumers.